Association Of Attitudes Towards Euthanasia With Religiosity, Emotional Empathy And Exposure To The Terminally Ill - Waqas, Ahmad; Fatima, Noor; Lodhi, Haneen Wajid; Shareef, Waqar; Ilahi, Maham (Journal of Pakistan Psychiatric Society, 2015)
Abstract